Sustainable Development Goals (SDGs) 9: Industry, Innovation, and Infrastructure during the COVID-19 Pandemic in Indonesia - Nauli, Bunga Putri (Jurnal Hubungan Internasional, 2022)
Indonesia is one of the countries affected by the COVID-19 pandemic. This pandemic has caused global countries to experience a decline in the index for sustainable development goals. Indonesia and other countries have committed to meeting sustainable development goals in infrastructure, industry, and innovation (SDGs 9). This study aims to explore the implementation of SDGs 9 during the COVID-19 pandemic. This study applied a qualitative approach in describing the results of the study. The study results disclosed that before the COVID-19 pandemic hit, the achievement of SDGs 9 still had to be accelerated. When COVID-19 hit, the achievement of SDGs 9 decreased. In addition, the pandemic has reduced the availability of funds for various sectors because the government must focus on the health sector and efforts to mitigate COVID-19. As a result, there was a decrease in the budget for the implications of the SDGs. Over the past five years, innovations in infrastructure have continued to be carried out to support accessibility, mobility, integration and connectivity between regions in Indonesia, especially Eastern Indonesia, the smallest islands, the foremost and outermost islands of Indonesia. Connectivity also aims to support industrial sectors that benefit GDP and create massive jobs.